Peran Ibu Asuh dalam Mengimplementasikan Budaya Berbahasa Inggris di Lembaga Pengembangan Bahasa Asing Nurul Jadid - Imania Imania; Moh. Rifa'i (PALAPA, 2019)
The purpose of this paper is to find out how the Foster Mother owns the role to assist and become a leader to cultivate English in the Foreign Language Development Institution, so that the English-language culture of students can take part in this era by preaching religious knowledge in English. With its role, Foster Mother as a determinant of success of institutional students run with management functions which include: Planning, organizing, movement, control and evaluation. As well as foster mothers also play with their role, such as using a democratic style, providing motivation and giving awards to students so that students can carry out an English-language culture within the Foreign Language Development Institution. And in the English-speaking environment Nurul Jadid Islamic Boarding School has the characteristic which always be use English for about 24 hours in a day, conducting intensive studies, and speaking English with Islamic values. This research use desciptive qualitative approach. Data collection conducted by researchers is interview techniques. The object of research is the English-language culture which in this case is the leadership role of the Guardian Asuh.